Representation of Automata by Groups. II - Skobelev, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain necessary and sufficient conditions under which the representation of abstract automata in terms of finite groups is consistent with the transition function of an automaton. We obtain sufficient conditions under which the mapping of a free semigroup of an automaton into a group realized by a component of the representation is a homomorphism.